(untitled) (Alternautas, 2022)
A vast amount of literature has investigated the conflicts between different ways of conceiving development in Latin America. Particular attention has been paid to power differentials among knowledge systems when it comes to decision-making, values and practices over water resources. The Ecosystem Services framework or Integrated Water Resources Management (IWRM) are often analysed as examples of technical and scientific tools typically produced by multilateral organizations, cooperation agencies and international experts. They are presented as discourses competing with environmental and water justice claims, or local and traditional knowledge, although they can sometimes support them and/or try to incorporate them. The question that arises is whether such incorporation depoliticises local understandings of sustainability and development. This paper aims to examine both the synergies and tensions among different forms of knowledge around development through one empirical case study in the Ecuadorian highlands. It focuses on the efforts of the Kayambi indigenous communities to create, negotiate and scale-up a water conservation funding scheme based on reciprocity and solidarity values. This contribution highlights the creative engagement of diverse actors in designing, cocreating and diffusing a diversity of perspectives on development. It challenges the frontiers between technoscientific and grassroots knowledge by paying attention to the situated practices of different actors. It argues that the coproduction of water and development knowledge between various actors is the result of negotiating worldviews possibly in tension and moving beyond traditional resistance.